Clinical characteristics and outcomes of infective endocarditis: impact of haemodialysis status, especially vascular access infection on short-term mortality. Issue 9 (2nd September 2021) - Kwon, Seong Soon; Park, Se Yoon; Bang, Duk Won; Lee, Min-Ho; Hyon, Min-Su; Lee, Seong Soo; Yun, Sangchul; Song, Dan; Park, Byoung-Won
Abstract: Background: Patients on haemodialysis (HD) are at high risk of infective endocarditis (IE). Research comparing the microbiological features as well as clinical characteristics and outcomes of HD and non-HD patients with IE is limited. Specifically, no data focussed on vascular access infections (VAIs) have been reported. Methods: The medical records of patients with IE were retrospectively reviewed from January 2010 to February 2020 in a referral hospital in Korea. Those with definite or possible IE by modified Duke criteria were included in the study. The clinical characteristics, microbiological features, echocardiographic findings and outcomes of the patients were analysed. Results: Of the 80 patients with IE, 34 had undergone HD and 46 had not. HD patients with IE had a higher in-hospital mortality rate (50% vs. 17.4%, p = .004) than non-HD patients. In multivariable stepwise Cox proportional hazards regression analysis, HD (hazard ratio = 2.633; 95% confidential interval: 1.053–6.582; p = .038) was predictors of 60-day mortality in IE patients. In HD patients, the presence of VAI was associated with a high in-hospital mortality rate (70.59% vs. 29.41%, p = .039) and all of the patients with VAIs (100%) had methicillin-resistant S. aureus (MRSA) as a causative pathogen. Conclusions: HD patients with IE showed high in-hospital mortality. HD, high C-reactive protein levels and lower left ventricular ejection fraction were predictors of 60-day mortality in IE patients. In particular, HD patients with VAIs had higher mortality rates and MRSA should be considered as the causative microorganism.